2020
DOI: 10.1136/openhrt-2020-001356
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between hyperinsulinaemia, magnesium, vitamin D, thrombosis and COVID-19: rationale for clinical management

Abstract: Risk factors for COVID-19 patients with poorer outcomes include pre-existing conditions: obesity, type 2 diabetes mellitus, cardiovascular disease (CVD), heart failure, hypertension, low oxygen saturation capacity, cancer, elevated: ferritin, C reactive protein (CRP) and D-dimer. A common denominator, hyperinsulinaemia, provides a plausible mechanism of action, underlying CVD, hypertension and strokes, all conditions typified with thrombi. The underlying science provides a theoretical management algorithm for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 92 publications
0
72
0
5
Order By: Relevance
“…This could lead to dysfunction of endothelial cells, resulting in excessive thrombin formation 19 . Pulmonary thrombin could even be responsible for oxygen desaturation and acute respiratory distress commonly observed in COVID‐19 patients 20‐22 . Elevated D‐dimer levels were reported to represent a hypercoagulable state in COVID‐19 patients 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to dysfunction of endothelial cells, resulting in excessive thrombin formation 19 . Pulmonary thrombin could even be responsible for oxygen desaturation and acute respiratory distress commonly observed in COVID‐19 patients 20‐22 . Elevated D‐dimer levels were reported to represent a hypercoagulable state in COVID‐19 patients 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant effect on TMPRSS2 methylation was observed among those aged 65 years or older, it is likely Mg treatment may exert benefits through other mechanisms. First, our and other studies found Mg optimized body vitamin D status and substantially reduced the doses requirement for vitamin D [9,18,66]. Vitamin D has been proposed to generate beneficial effects in ARDS through activation of the vitamin D receptor (VDR) signaling pathway by reducing the cytokine storm, regulating the renin-angiotensin system, maintaining the integrity of the pulmonary epithelial barrier, and tapering down the increased coagulability [16].…”
Section: Discussionmentioning
confidence: 97%
“…Dysregulation of the ACE2 pathway in the pancreas causes β-cell dysfunction and induces hyperglycemia [ 69 ]. The latter [ 28 ] and hyperinsulinemia [ 70 ] play a crucial role in thrombo-inflammation during COVID-19 infection. Countries with higher and lower death rates for COVID-19 appear to have high consumptions of fats and cereal, respectively [ 71 ].…”
Section: Diabesity Meta-inflammation and Il-6: The Role In Severmentioning
confidence: 99%